High-harmonic spectroscopy of ultrafast many-body dynamics in strongly correlated systems - Silva, R. E. F.; Blinov, Igor V.; Rubtsov, Alexey N.; Smirnova, Olga; Ivanov, Mikhail (Nature Photonics, 2018)
We bring together two topics that, until now, have been the focus of intense but non-overlapping research efforts. The first concerns high-harmonic generation in solids, which occurs when an intense light field excites a highly non-equilibrium electronic response in a semiconductor or a dielectric. The second concerns many-body dynamics in strongly correlated systems such as the Mott insulator. We show that high-harmonic generation can be used to time-resolve ultrafast many-body dynamics associated with an optically driven phase transition, with accuracy far exceeding one cycle of the driving light field. Our work paves the way for time-resolving highly non-equilibrium many-body dynamics in strongly correlated systems, with few femtosecond accuracy.
CRIS-Team Scopus Importer:2023-04-20